Challenges to a Rights-Based Approach in Sexual Health Policy: A Comparative Study of Turkey and England - Volkan Yilmaz; Paul Willis (Societies, 2020)
Politics around sexual health have been polarised in recent years, but the policy implications of this polarisation have not yet been examined in depth. Therefore, this article explores political challenges to a rights-based approach in sexual health policies in Turkey and England. Its focus is on two domains: The prevention and treatment of sexually transmitted infections (STI), and sexual health education. Drawing on an interpretive documentary analysis, this article reveals that although social attitudes to sexuality and the levels of overall alignment with a rights-based framework within the selected countries do differ, both face significant political challenges in putting a rights-based approach to sexual health into practice. While common political challenges include heightened domestic controversy regarding sexual health, the specific challenges take the forms of a broader conservative turn that undermines the autonomy of sexual health policy in Turkey (similar to the cases of Hungary and Poland), and neoliberal policy preferences coupled with local discretion and service fragmentation that create access inequities in England (similar to the case of Germany). This study concludes that implementing a rights-based approach is a complex political task requiring a nuanced approach that incorporates the political dimension.